Design of Stopwatch based on STC89C52 Single Chip Microcomputer - Wei, Wang; Yongjian, Sun (Journal of Current Scientific Research, 2022)
This design is according to the requirements of the wide rider, and the Multi-function bike computer has the function of velocity measurement, display, timing, lighting, buzzer warning, which could satisfy the requirements of cycling enthusiasts. This design is based on STC89C52 SCM (Single Chip Microcomputer) smallest system and uses hall sensor receives the bicycle wheel rotation numbers date, and then transmit the received data into the SCM. After the SCM’s calculation and processing, it gets the bicycle’s instantaneous speed, mileage, riding time through the LED display the date. The part of software programming use C language, which compiles and downloads by the Keil and STC-ISP. This design uses Proteus to make the circuit diagram drawing and system simulation. The overall program adopted modular approach, and each module has a special function. The idea which makes the program more clear, is advantageous to the optimization of code logic and modification.
Keywords: Microcomputer; LED; Proteus